2015
DOI: 10.1002/bies.201500068
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived microvesicles in the tumor microenvironment: How vesicle heterogeneity can shape the future of a rapidly expanding field

Abstract: Information transmission from tumor cells to non-tumor cells in the surrounding microenvironment via microvesicles is a more recently studied form of intercellular signaling that can have a marked impact on the tumor microenvironment. Tumor-derived microvesicles (TMVs) are packed with information including signaling proteins and nucleic acids, and can be taken up by target cells, enabling paracrine signaling. While previous research has focused on how vesicles released from pathologic cells differ from normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Finally, given the plethora of macromolecular cargo content found within microvesicles, it is worth noting that similar to what has been described for exosomes, 22 there are likely heterogeneous pools containing distinct cargo within the total microvesicle population. 23,24
Figure 1. Common biological functions of microvesicle protein cargo identified in Vesiclepedia database.
…”
Section: Introductionmentioning
confidence: 99%
“…Finally, given the plethora of macromolecular cargo content found within microvesicles, it is worth noting that similar to what has been described for exosomes, 22 there are likely heterogeneous pools containing distinct cargo within the total microvesicle population. 23,24
Figure 1. Common biological functions of microvesicle protein cargo identified in Vesiclepedia database.
…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that MV participate in the regulation of target cell function. Moreover, they are involved in clotting [64,69], inflammatory [2,67], immune response [63], neogenesis [8,32,45], and carcinogenesis [3,11,50] processes. Among numerous cells being the source of MV, leukocytes are of particular interest due to the diversity of their receptor and effector functions.…”
mentioning
confidence: 99%
“…Several studies revealed that TMVs transport cancerous molecules to recipient cells, which eventually contribute to tumor progression and metastasis [11][12][13][14]76] [Figure 2]. Interestingly, the transport of anti-cancer drugs out of ovarian cancer cells through their secreted EVs supported the role of EVs in cancer progression and treatment.…”
Section: Mvs: the Tiny Mediators In Intercellular Communicationmentioning
confidence: 99%
“…A reduction in cancer cell stemness was recorded by inhibiting the paracrine behavior of CAFs [ 84 ] . Conversely, TMVs have been shown to activate CAFs to improve the mobility of tumor cells, while the activated fibroblasts could secret MVs and in turn facilitate tumor progression [ 12 , 85 ] . Moreover, small GTPases and RHO-associated protein kinase, key factors in the biogenesis of MVs [ 73 ] , were found to be highly expressed in both CAFs and cancer cells [ 86 ] , which indicates the possible role of CAFs in the alteration of MVs secretion.…”
Section: The Dynamic Impact Of Mvs On Sorafenib Resistancementioning
confidence: 99%
See 1 more Smart Citation